Landward zones of mangroves are sinks for both land and water borne anthropogenic debris - Luo, Ying Y.; Vorsatz, Lyle D.; Not, Christelle; Cannicci, Stefano (The Science of the total environment, 2022)
The hotspots for mangrove diversity and plastic emissions from rivers overlap in Asia, however very few studies have investigated anthropogenic marine debris (AMD) pollution in these threatened coastal ecosystems. Despite Hong Kong's position at the mouth of the Pearl River, a major source of mismanaged waste in Asia, the mangroves in Hong Kong have never been extensively surveyed for AMD. Here we assessed the patterns of AMD abundance within 18 mangrove forests across Hong Kong surveying both their landward and seaward zones. We recorded and categorised, according to their material and potential uses, both the amount of debris items and area they covered, to better quantify its potential impact on the mangroves. Across Hong Kong mangroves, the average abundance of debris was 1.45 ± 0.38 (SE) items m−2, with an average coverage of 6.05 ± 1.59%. Plastic formed a high proportion of AMD accounting for 70.31% by number of items and 49.71% by area covered, followed by glass/ceramics and wood/bamboo. Disposable food packaging, fishing gear and industrial and construction related waste were the major sources of AMD we documented. On average, we recorded about six times more debris items m−2 at the landward sites than at the seaward one, but these abundances varied between the East and the West coastlines of Hong Kong. Our data confirms the hypothesis that landward areas of mangrove forests act as traps and retain marine borne debris, but they also suggest that direct dumping of waste from the land could represent a serious impact for these forests placed in between the land and the sea. More research is needed to ascertain the impact of land disposed debris on mangrove degradation, and this study strongly advocates for a cultural shift about the perception of these forests by the public. [Display omitted] •Mangrove forests are understudied traps for anthropogenic marine debris (AMD).•Sparse data are available on the impact of AMD on mangroves of the South China Sea.•Plastic made up the majority of items by count and surface area smothered.•Fishing, food and industry related items formed >55% of items counted and measured.•Debris was about six times more abundant at the landward than at the seaward belt.